Desafios de conexão entre startups e empresas do varejo farmacêutico brasileiro - Gessé Gerônimo Pereira Evangelista (2022)
The objective of the present work was to identify and analyze the main barriers arising from the connection between startups with Brazilian pharmaceutical retailers from the perspective of startup founders. For this, the research was divided into two parts: the first being an analysis of secondary data, based on the identification of startup-industry connection initiatives in the main search engines, followed by an empirical study, of a qualitative nature, directly with the founders of startups who were involved in engagement initiatives with large pharmaceutical retail companies. Throughout the work, the complementarity between startups and large corporations became noticeable as a great open innovation strategy currently practiced, as well as such practice being used as an open innovation strategy by the main global corporations. This movement is also perceived within pharmaceutical retail and may have been boosted due to the COVID-19 pandemic, which can be seen by the volume of engagement initiatives with startups that were computed in the survey carried out. The analyzes also showed major challenges that permeate the absence of a strategy for interaction with startups, which presented itself as a barrier factor in the first connection between the parties, as well as the difficulty of dealing with disruptive innovation and with innovations that are generated outside the company, where the lack of understanding of the application of startups in everyday life impacts the perception of value and generation of results. of engagement, based on the insights found in the challenges of connection between both parties.